Pediatric Crohn’s disease complications. - Casella, P; Alves, F; Cabral, J (Acta Médica Portuguesa, 1998)
This case report describes our experience in treatment of a child with Crohn’s disease involvement of ileocecal and sigmoid regions complicated with a severe abdominal wall abscess. A combined therapeutic approach of the acute episode was based on intestinal diversion, abscess drainage, antibiotherapy, nutritional support and post-operative immunosuppression with azathioprine. The definitive treatment of the ileocolonic involvement occurred 6 months after the acute episode and consisted of limited resection, multiple strictureplasties, primar" closure of ileosigmod fistula and undiversion. This operative procedure was followed by a short period of total parenteral nutrition and progressive re-establishment ofenteric nutritional support and immunosuppression. At 18 months follow-up, under low dose azathioprine revealed, a normal growth with a 20 Kg weight gain and 10 cm height gain, no evidence of fistula recurrence or restenosis and suggests the safety of strictureplasty in paediatric patients as a way to conserve as much small bowel as possible.